Optimization of Solid-Supported Glaser-Hay Reactions in the Microwave - Jessica S. Lampkowski; Johnathan C. Maza; Sanjana Verma; Douglas D. Young (Molecules, 2015)
The translation of organometallic reactions into a microwave reactor has numerous advantages. Herein, we describe the application of a previously developed solid-supported Glaser-Hay reaction to microwave conditions. Overall, an array of diynes has been prepared demonstrating the ability to conduct chemoselective reactions in the microwave within 20 min compared to the 16 h thermal conditions. Moreover, non-microwave transparent alkynes have been found to react more quickly, preventing catalyst quenching, and resulting in higher yields.